Efficient Mixed Generative Using Semantic Cross Media Hashing Methods - Jadhav, P.T; Sonkamble, S.B (International Journal of Computer Sciences and Engineering, 2018)
Hash methods are useful for number of tasks and have attracted large attention in recent times. They proposed different approaches to capture the similarities between text and images. Most of the existing work uses bag-of-words method to represent text information. Since words with different format may have same meaning, the similarities of the semantic text cannot be well worked out in these methods. To overcome these challenges, a new method called Semantic Cross Media Hashing (SCMH) is proposed that uses the continuous representations of words which captures the semantic textual similarity level and uses a Deep Belief Network (DBN) to build the correlation between different modes. In this method we use Skipgram algorithm for word embedding, Scale Invariant Feature Transform(SIFT) descriptor to extract the key points from the images and MD5 algorithm for hash code generation. To demonstrate the effectiveness of the proposed method, it is necessary to consider data sets that are basic. Experimental results shows that the proposed method achieves significantly better results as well as the effectiveness of the proposed method is similar or superior to other hash methods.